1988
DOI: 10.1111/j.1600-0676.1988.tb00966.x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Ito cells in experimental hepatic fibrosis

Abstract: Ito cells (FSC) have been thought to be collagen-producing cells with regard to hepatic fibrosis. We have found that desmin, a structural protein of muscular intermediate filaments, is found in the cytoplasm of FSC, even in negative vitamin Aautofluorescence FSC, by using immunocytochemical techniques. In the present study, numbers of FSC produced by the administration of heterogeneic serum or carbon tetrachloride were detected in fibrous and non-fibrous areas of hepatic lobules by using a morphometrical anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

1989
1989
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(11 citation statements)
references
References 11 publications
0
9
0
2
Order By: Relevance
“…Radiation-induced liver disease (RILD) typically occurs 4-8 weeks after the completion of treatment, although it has been described as early as 2 weeks and as late as 7 months [29,30]. After any type of liver injury, hepatic stellate cells proliferate in the affected sites and undergo a myofibroblastic transformation preceding the production of extracellular matrix and hepatic fibrosis [31,32]. Those activated hepatic stellate cells are rarely seen in non-irradiated liver parenchyma.…”
Section: Discussionmentioning
confidence: 99%
“…Radiation-induced liver disease (RILD) typically occurs 4-8 weeks after the completion of treatment, although it has been described as early as 2 weeks and as late as 7 months [29,30]. After any type of liver injury, hepatic stellate cells proliferate in the affected sites and undergo a myofibroblastic transformation preceding the production of extracellular matrix and hepatic fibrosis [31,32]. Those activated hepatic stellate cells are rarely seen in non-irradiated liver parenchyma.…”
Section: Discussionmentioning
confidence: 99%
“…When activated, HSCs transform into myofibroblast-like cells. Since the first report by Yokoi et al [29], desmin has frequently been used as a marker of HSCs and reflecting the proliferation kinetics of HSCs after CCl 4 intoxication or bile duct ligation. In addition, amount of evidences demonstrated that the expression of a-SMA is a reliable and widely used marker of activation of HSCs [30], [31].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there is an increase in stellate cells in the perivenular region prior to the development of fibrous septa. 557,558 These findings indicate that simultaneous alterations in stellate cells, extracellular matrix, and the parenchymal microvasculature occur during the evolution of cirrhosis. Put differently, microvascular changes are not merely the consequence of fibrosis and nodule formation, but are part of the evolution of cirrhosis.…”
Section: The Role Of Progenitor Cellsmentioning
confidence: 92%